Management of Agroindustrial Lignocellulosic Wastes through Vermitechnology and Production of Agronomic Valid Vermicompost - Prashija, K.V.; Parthasarathi, Kasi (International Journal of Biotechnology for Wellness Industries, 2016)
We aimed to recycle the agroindustrial waste resources- pressmud(PM), sugarcane trash (ST) and biomethanated distillery effluent(BE) and produced agronomic valid vermicompost using earthworm, Perionyx excavatus for maintaining natural soil organic and sustainable agricultural activity. Therefore, a series of studies were carried out to convert PM-ST-BE in different proportion vermibeds (T1-1000g PM+0g ST+790ml BE), (T2- 900g PM+100g ST+740ml BE), (T3-800g PM+200g ST+696ml BE), (T4-700g PM +300g ST+655ml BE), (T5-600g PM+400g ST+625ml BE) and (T6-500g PM+500g ST+542ml BE) into vermicompost. The study was to examine the activity of earthworm- growth, reproduction, vermicompost recovery and its nutrient status. The pronounced and better worm activity was found in all vermibeds, especially more in T1 and T3 vermibeds followed by others. This seems to be due to rich cellulose, OC, N, P, microbial activity, enhanced water holding capacity and palatability of the substrates. Enhanced microbial activity, humic acid content, NPK, normalized pH, declined OC, C-N, and C-P ratio, lignin, cellulose, hemicellulose and phenol in vermicompost than normal compost and control. The increased microbial-enzymatic activities contribute an increase in nutrients through nitrification, phosphate solubilization and mineralization. Reduction of OC, C-N, C-P ratio, lignin, cellulose, hemicellulose and phenol in the vermicompost are due to combined action of gut microflaura and earthworm during the vermicomposting process and utilization of these contents by the worm for their growth and reproduction. Finally, our study recommended for the production and application of vermifertilizer from lignocellulosic wastes using vermitechnology for sustainable activity.